Exploring the immunomodulatory effects and mechanisms of Xinjiang fermented camel milk-derived bioactive peptides based on network pharmacology and molecular docking - Wang, Yuxing; Liang, Zhuangzhuang; Shen, Fang; Zhou, Wenting; Manaer, Tabusi; Jiaerken, Didaier; Nabi, Xinhua (Frontiers in Pharmacology, 2023)
Abstract: Purpose: Fermented camel milk from Xinjiang is rich in probiotics and has immunomodulatory effects as an important source of bioactive peptides. However, it is not clear whether it is the probiotic or the bioactive peptide that acts. The present study aimed to extract and identify bioactive peptides from fermented camel milk in Xinjiang and investigate their immunomodulatory effects and mechanisms based on network pharmacology and molecular docking. METHODS: Four probiotic bacteria were used to ferment the fresh camel milk and the active peptides were extracted and isolated by ultrafiltration and column chromatography. Network pharmacology predicts targets and pathways of action. GeneCards and OMIM-GENE-MAP database were used in order to search disease target genes and screen common target genes. Then we used STRING web to construct a PPI (protein-protein interaction) interaction network of the common target protein. The key targets were analyzed by GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis through the David database. The "drug-disease-targets-pathway" network was established and molecular docking was used for prediction. Results: Two fractions were obtained by UV spectrophotometer; whey acidic protein, α-lactalbumin, and peptidoglycan recognition protein 1 were the main protein-like components of Xinjiang fermented camel milk-derived bioactive peptides. The repeat sequence of peptidoglycan recognition protein 1 was selected and then seven active peptides were obtained. Active peptides had 222 gene targets, anti-inflammatory diseases had 2598 gene targets, and immune regulation had 866 gene targets, the intersection of which was 66 in common gene targets. GO and KEGG analysis reveals that active peptides mainly play a vital role in the signaling pathways of lipid and atherosclerosis, pathways in cancer. The molecular docking results showed that the seven active peptides bound well to the top four scoring proteins. Conclusion: The immunomodulatory and anti-inflammatory effects and mechanisms of Xinjiang fermented camel milk-derived bioactive peptides were initially investigated by network pharmacology and molecular docking, providing a scientific basis for future studies.